Long-Term Dynamics of New Residential Supply: A Case Study of the Apartment Segment in Sweden - Sviatlana Engerstam; Abukar Warsame; Mats Wilhelmsson (Buildings, 2022)
Since the size of the homeownership ratio differs significantly between countries, it is important to understand the mechanisms that lie behind the decrease or growth of certain sectors of the housing market such as rentals and housing cooperatives. The aim of this study is to analyze the long-term dynamics of the new residential supply in Sweden’s three largest cities for the period of 1990–2020 and estimate in what way market fundamentals affect it through new construction and housing conversions. We apply panel data methodology and, in distinction to previous research, consider the development of the housing market (urban growth) as physical volume. The results demonstrate that structural changes are driven mainly by fundamental demand factors and that the displacement effect occurs primarily in the market’s rental sector and not in the owner-occupied segment. The apartment price per square meter, together with mortgage interest rates, are the major driving factors in the process of converting dwellings into housing cooperatives. Fundamental variables that affect new construction in both the rental and housing cooperative sectors are population and income growth. In the presence of a rent control environment, the rent or price level does not contribute to adding new units to the total housing stock.